2004
DOI: 10.1111/j.1468-3156.2004.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of social stories in a psychology service for children with learning disabilities: a case study of a sleep problem

Abstract: This paper overviews the phenomena of social stories in conveying social messages to children with autistic spectrum disorder and learning disabilities. The use of social stories in a clinical psychology service for children with predominantly severe learning disabilities is discussed. A case study is presented describing the use of a social story as part of a conventional behavioural intervention on a boy presenting problems surrounding sleep behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 8 publications
0
52
1
Order By: Relevance
“…Studies have demonstrated that social stories have been useful for children with autism as young as 4 years (Cullain 2000;Moore 2004;Romano 2002;Salazar 2004) and as old as 16 years in age (Gray and Garand 1993). Interestingly, social stories have also been shown to be effective with typically developing children (Burke et al 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies have demonstrated that social stories have been useful for children with autism as young as 4 years (Cullain 2000;Moore 2004;Romano 2002;Salazar 2004) and as old as 16 years in age (Gray and Garand 1993). Interestingly, social stories have also been shown to be effective with typically developing children (Burke et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Gray (1995Gray ( , 1998Gray ( , 2000 added more sentences including: (a) control, (b) affirmative, (c) cooperative and (d) partial sentences. To date, most of the social story literature used Gray's (1995) ''basic'' ratio that includes 1 directive and/or control sentence for every 3-5 descriptive and/or perspective sentences (Adams et al 2004;Agosta et al 2004;Bäckman and Pilebro 1999;Barry and Burlew 2004;Brownell 2002;Cullain 2000;Feinberg 2001;Gray and Garand 1993;Hagiwara 1998;Hagiwara and Myles 1999;Ivey et al 2004;Kuttler et al 1998;Lorimer et al 2002;Moore 2004;Norris and Dattilo 1999;Pettigrew 1998;Rogers and Myles 2001;Romano 2002;Rowe 1999;Scattone 2002;Scattone et al 2002;Staley 2001;Swaggart et al 1995;Thiemann and Goldstein 2001). Although Gray (2000) and Gray and Leigh White (2002) continues to endorse the use of a growing number of types of sentences in social stories, research has not yet examined which ratio of different sentence types is most effective.…”
mentioning
confidence: 99%
“…To maximise success, they need the guidance of teachers or others trained in using social stories. Decades of research emphasises the importance of providing ongoing support to teachers or clinicians and parents (or caregivers) when using social stories to help individuals with ASDs develop and maintain desired social-emotional skills (Kuttler, Myles, & Carlson, 1998;Lorimer et al, 2002;Moore, 2004;Ozdemir, 2008;Reynhout & Carter, 2007;Rogers & Myles, 2001;Sansosti & Powell-Smith, 2008). All the participants interviewed for this study strongly recommended some form of education or training for teachers on using social stories to help students with ASDs develop and maintain desired social skills.…”
Section: Discussionmentioning
confidence: 93%
“…Social stories have been used with a great deal of success to help individuals with ASDs in a variety of settings (Agosta et al, 2004;Ali & Frederickson, 2006;Barry & Burlew, 2004;Bledsoe, Myles, & Simpson, 2003;Gray & Garand, 1993;Ledford & Wolery, 2013;Lorimer, Simpson, Myles, & Ganz, 2002;Moore, 2004;Plavnick et al, 2013;Rowe, 1999;Whitehead, 2007). Whatever the medium, the primary goal is to find or create stories that will best help individuals with ASDs develop social skills.…”
Section: Discussionmentioning
confidence: 98%
“…The corresponding percentage for children with ASD (14.3%) was also lower in the present study than the percentages produced by other studies. Intervention programs (Howlin, 1984;Moore, 2004;Reed et al, 2009;Weiskop et al, 2005) are intended to eliminate such behaviors in individuals with ASD. To draw an overall conclusion for the test sample, it may be stated that the parents of TD children believe that their offspring do not experience any disorders that might impair their sleep.…”
Section: Discussionmentioning
confidence: 99%